Novel solar absorber surfaces with organic pigments - Nunes, Clarisse (2010)
This paper presents results of application of natural and synthetic organic pigments in selective solar absorber coatings. Some of these photo excite pigments were tested like solar radiation absorber pigments in paint coatings and others as a form to increase the absorption of solar radiation in titanium oxide monolayer selective coatings produced by reactive magnetron sputtering. Morphologic aspects and optical properties are discussed as a function of deposition parameters and of formulation parameters. The main goal is to prepare solar absorber surfaces as a tandem of TiOx thin films, organic pigment using a conductive substrate or of paint with organic and/or inorganic pigments and conductive substrate, all reaching great photo thermal conversion efficiency, high durability and low costs to the ending product and stability at medium range temperatures (120-150ºC). The best optical properties for titanium oxide sputtered films were 88% for solar absorption, with 7% of emissivity for deposition parameters of: pulsed frequency 200kHz, reverse time of 0.4μs, discharge current of 0.7A, argon flow rate of 50ml/min and oxygen flow rate changing from 0 to 2.5ml/min. The results obtained with paints were not satisfactory. The best couple values for solar absorption and emissivity were respectively 94%, and 74%